'Extremely valuable work': British intelligence and the interrogation of refugees in London, 1941–45. Issue 1 (2nd January 2021) - Photiadou, Artemis Joanna
ABSTRACT: This article focuses on the compulsory questioning of over 30, 000 refugees who escaped to Britain during the Second World War and who were detained in London's Royal (Victoria) Patriotic School. It answers three questions: how did intelligence come to see non-British civilians as sources; what characteristics did refugees possess and how did these influence the information they shared; and who was interested in their accounts? It argues that, while this site was set up as an MI5 vetting camp for the identification of Axis agents, it quickly evolved into an intelligence-gathering centre, serving the interests of multiple departments and organisations.